Olfactory transport efficiency of the manganese oxide nanoparticles (II) after their single or multiple intranasal administrations - A. V. Romashchenko; M. B. Sharapova; D. V. Petrovskii; M. P. Moshkin (Вавиловский журнал генетики и селекции)
In experiments with reusable inhalation of nano-sized metal oxide particles, it has been shown that there is no significant relationship between the number of presentations and the metal concentration in the olfactory bulb. This fact raises the question of a possible decrease in the efficiency of particulate capturing by the olfactory epithelium after their repeated application into the nasal cavity. In this study, we compared the effectiveness of nasal transport of paramagnetic nanoparticles after their single and multiple intranasal administration and evaluated their effects on the morphological and functional characteristics of the olfactory system. Based on the data, the accumulation of MnO-NPs in the olfactory bulb of mice was reduced after repeated intranasal application. In addition, the decrease in the efficiency of olfactory transport observed after repeated administration of MnO-NPs was partially restored by intranasal application of mucolytic (0.01 M N-acetyl-L-cysteine). In this case, the concentration of particles in the olfactory bulb was proportional to the volume of the structure, which in particular depends on the number of synaptic contacts between the mitral cell of the olfactory bulb (OB) and olfactory epithelium (OE). It should be noted that multiple intranasal injections of MnO-NPs reduce mouse OE thickness. Thus, repeated intranasal introduction of MnO-NPs reduces the efficiency of nanoparticle olfactory transport from the nasal cavity to the brain, which is combined with the increase in the viscosity of the mucosal layer and the reduction in the number of synaptic contacts between OB and OE. These results indicate the presence of the natural mechanisms of protection against the penetration of pathogens and xenobiotics into the olfactory epithelium; they also allow us to formulate practical recommendations on intranasal drugs delivery.